2018
DOI: 10.1186/s12888-018-1835-3
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of epidemiology of depression in people living with HIV in east Africa

Abstract: BackgroundDepression is the most prevalent psychiatric disorder among people living with HIV (PLWHIV) and is associated with poor quality of life, additional comorbidities, disability, unemployment, poorer therapeutic outcomes and risky behaviors. The present systematic review and meta-analysis aims to systematically summarize empirical evidence and to formulate recommendations for future research.MethodsWe searched PubMed, EMBASE, SCOPUS, and relevant literature for possible studies to include. A qualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
55
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 39 publications
10
55
2
1
Order By: Relevance
“…However, to our surprise, only 13.2% of nurses in Vietnam have depression [55], as well as 24.9% of Iranian nurses working in military hospitals [56]. In addition, the Chinese nurses even seem to have higher prevalence of depression than some special populations, such as people living with HIV with 38% [57], outpatients with 27.0% [58], and Indian elderly population with 34.4% [59]. Therefore, we may conclude that Chinese nurses were at a particularly high risk of having depressive symptoms.…”
Section: Plos Onementioning
confidence: 99%
“…However, to our surprise, only 13.2% of nurses in Vietnam have depression [55], as well as 24.9% of Iranian nurses working in military hospitals [56]. In addition, the Chinese nurses even seem to have higher prevalence of depression than some special populations, such as people living with HIV with 38% [57], outpatients with 27.0% [58], and Indian elderly population with 34.4% [59]. Therefore, we may conclude that Chinese nurses were at a particularly high risk of having depressive symptoms.…”
Section: Plos Onementioning
confidence: 99%
“…A systematic review of studies from SSA found a range of 9 to 32% prevalence of probable depression [ 10 ]. A meta-analysis of studies from East Africa indicated a 38% pooled prevalence of probable depression [ 11 ]. A systematic review of studies from Ethiopia reported a 37% pooled prevalence of probable depression among PLWHA [ 12 ] which was much higher compared to the 11% pooled prevalence in the general population [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, living with HIV significantly increased MD among participants. Previous study noted that HIV significantly increase the risk of MD and that relationship between HIV and MD is mediated through more than 10 risk factors for depression (33). Additionally, being 30+ years of age (older age) was found to significantly increase MD.…”
Section: Discussionmentioning
confidence: 81%